2009
DOI: 10.1212/wnl.0b013e3181ad5387
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar magnetic stimulation decreases levodopa-induced dyskinesias in Parkinson disease

Abstract: Our study demonstrates that cerebellar continuous theta burst stimulation has an antidyskinetic effect in Parkinson disease patients with levodopa-induced dyskinesia, possibly due to modulation of cerebellothalamocortical pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 39 publications
6
138
0
3
Order By: Relevance
“…The present study confirms and extends our previous results demonstrating the antidyskinetic effect of cerebellar cTBS in PD patients with LID [12]. We found that a week of bilateral cerebellar cTBS was able to induce a reduction of LID; clinical changes were paralleled by a reduction of FDG metabolism in the cerebellum as revealed by PET imaging.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study confirms and extends our previous results demonstrating the antidyskinetic effect of cerebellar cTBS in PD patients with LID [12]. We found that a week of bilateral cerebellar cTBS was able to induce a reduction of LID; clinical changes were paralleled by a reduction of FDG metabolism in the cerebellum as revealed by PET imaging.…”
Section: Discussionsupporting
confidence: 92%
“…This in turn leads to an inhibition of the contralateral cerebral cortex, due to a reduction in dentato-thalamo-cortical facilitatory drive [28]. Therefore, our findings seem to confirm the hypothesis that the motor cerebellar circuit is involved in the generations of LIDs [12]. One intriguing possibility is that cerebellar cTBS may have expressed its antidyskinetic effect trough a direct modulation of the excitability of the cerebellar cortex.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Various stimulation paradigms including 1 Hz-repetitive transcranial magnetic stimulation (rTMS) (Buhmann et al, 2004), 5 Hz-rTMS (Mir et al, 2005), continuous Theta-Burst stimulation (cTBS) (Koch et al, 2009) and paired-associative-stimulation (PAS) (Morgante, Espay, Gunraj, Lang, & Chen, 2006) demonstrate preserved plasticity in PD, which may be maladaptive in the pathogenesis of dyskinesias (Morgante et al, 2006). The efficacy of transcranial stimulation is contingent on its ability to induce persistent effects with intermittent applications in direct contrast to the chronic stimulation used in DBS.…”
Section: Pathophysiology Of Parkinson's Diseasementioning
confidence: 99%
“…A number of studies have reported a therapeutic effect of rTMS in PD. rTMS can transiently infl uence PD abnormal motor functions (Filipovic et al, 2010;Hamada et al, 2008;Helmich et al, 2006;Khedr et al, 2006;Lefaucheur et al, 2004;Mally & Stone, 1999a, 1999bPal et al, 2010;Siebner et al, 2003) with a selective improvement for levodopa-induced dyskinesias (Filipovic et al, 2009;Koch et al, 2005Koch et al, , 2009, especially when high stimulation frequencies are used (Lefaucheur et al, 2004). rTMS at 1 Hz may also elicit a sustained or prolonged change in PD cortex excitability as revealed by a longer silent period duration (Filipovic et al, 2010) suggestive of an infl uence on GABA activity.…”
Section: Imaging Tms Effects In Pdmentioning
confidence: 99%